Climatology of NOy in the troposphere and UT/LS from measurements made in MOZAIC - Karin Thomas; Marcel Berg; Damien Boulanger; Norbert Houben; Alicia Gressent; Philippe Nédélec; Hans-Werner Pätz; Valerie Thouret; Andreas Volz-Thomas (Tellus: Series B, Chemical and Physical Meteorology, 2015)
In December 2000, a fully automatic NOy instrument was installed on one of the five Airbus A340 aircraft used in the MOZAIC project (Measurement of Ozone and Water Vapour by Airbus in-service Aircraft) for measurements of O3 and H2O since 1994. This long-range aircraft was operated by Lufthansa, mainly out of Frankfurt and Munich. After an initial testing period, regular data collection started in May 2001. Until May 2005, 1533 flights have been recorded, corresponding to 8500 flight hours of NOy measurements. Concurrent data of NOy and O3 are available from 1433 flights and concurrent data for CO, O3 and NOy exist from 1125 flights since 2002. The paper describes the data availability in terms of geographical, vertical and seasonal distribution and discusses the quality and limitations of the data, including interference by HCN. The vast majority of vertical profiles were measured over Frankfurt, followed by Munich and North American airports. While most of the data were collected in the upper troposphere and lower stratosphere over the North Atlantic, significant data sets exist also from flights to Far and Middle East, whereas data from the tropics and the Southern Hemisphere are relatively sparse.